Evaluation of Correlation between Salivary Calcium, Alkaline Phosphatase and Osteoporosis- A Prospective, Comparative and Observational Study - Mainak Kanti Saha; Prerna Agrawal; Suparna Ganguly Saha; Vinod Vishwanathan; Vandana Pathak; Sakuru Venkata Saiprasad; Purvi Dhariwal; Mahendra Dave (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Fixed and/or removable prosthodontics caters to the restorative needs of the largest count of geriatric patients whose rehabilitative procedures depend on the quality and quantity of available bone. The common diagnostic parameters for quantifying bone may involve an invasive blood examination, an expensive bone densitometry procedure or a urine analysis. Sialometry involving the basic biochemistry of saliva analysis may be proposed as an alternative to the conventional investigative protocol and its usefulness may be attributed owing to its non invasive and simpler procedure. Aim: The aim of this study was to compare the salivary calcium and alkaline phosphatase among osteoporotic, osteopenic and normal edentulous subjects. Materials and Methods: A prospective, comparative and observational study was carried out on 80 selected edentulous subjects (40 males and 40 females) aged 55-75 years (30 osteoporotic, 30 osteopenic and 20 control). A sample of saliva was taken for the study. Salivary calcium was measured by Arsenazo reaction; and alkaline phosphatase by the International Federation of Clinical Chemistry (IFCC) method. Statistical analysis was done by unpaired t-test. A comparison was made in the levels of salivary calcium and alkaline phosphatase with that of osteoporosis and osteopenia. Results: The mean salivary calcium and alkaline phosphatase levels were found to be significantly higher in the osteoporotic and osteopenic edentulous subjects as compared to the control group. Conclusion: Salivary calcium and alkaline phosphatase are increased significantly in case of osteoporosis and osteopenia. Hence, screening of salivary samples of patients may be an effective indicator for the detection of underlying disorders of bone metabolism.